Student perceptions on air conditioning practicum services in vocational education. Issue 6 (March 2021) - Berman, E T; Hamidah, I; Mulyanti, B; Setiawan, A
Abstract: This study aims to determine student perceptions of air conditioning practicum services in vocational education. The scope of practicum services study is laboratory facilities, human resources, and laboratory support components. This study uses survey methods to obtain data and quantitative descriptive methods to analyze data. The type of data in this study is mainly based on the responses of respondents representing the population of refrigeration and air conditioning study programs at a vocational education institution in Bandung, West Java, Indonesia. The results show that laboratories in vocational education can serve air conditioning practicum with good results. This study shows that laboratory facilities, human resources, and laboratory support components in vocational education can accommodate the implementation of air conditioning practices. In general, students stated that air conditioning practicum activities in the laboratory could be carried out well, even though the ratio between the number of equipment and students was still low and the evaluation of practicum activities was not yet comprehensive.